Prostate Stem Cell Compartments : Expression of the Cell Cycle Inhibitor p27(Kip1) in Normal, Hyperplastic, and Neoplastic Cells - De Marzo, Angelo M. (American Society for Investigative Pathology, 1998)
The stem cells of rapidly renewing tissues give rise to transiently proliferating cells, which in turn give rise to postmitotic terminally differentiated cells. Although the existence of a transiently proliferating compartment has been proposed for the prostate, little molecular anatomical evidence for its presence has been obtained to date. We used down-regulation of the cyclin-dependent kinase inhibitor p27(Kip1) to identify cells capable of entering the proliferative phase of the cell cycle and, therefore, competent to fulfill the role of the transiently proliferating compartment. We examined the expression of p27(Kip1) in relation to its role in the development of prostatic carcinoma. Formalin-fixed paraffin-embedded specimens from matched samples of normal-appearing prostate tissue, benign prostatic hyperplasia, high-grade prostatic intraepithelial neoplasia, primary adenocarcinomas, and pelvic lymph node metastases were evaluated by comparative immunohistochemistry against p27(Kip1). In normal-appearing prostate epithelium, moderate to strong nuclear staining of p27(Kip1) was present in greater than 85% of the terminally differentiated secretory cells. The normal basal cell compartment, believed to contain prostatic stem cells, showed distinctive p27(Kip1) expression; acini in epithelial benign prostatic hyperplasia tissue contained more p27(Kip1)-negative basal cells than acini from non-benign prostatic hyperplasia tissue. A third layer of cells was identified that was sandwiched between the basal cells and the luminal cells, and this layer was consistently p27(Kip1) negative. This intermediate layer was accentuated in the periurethral region, as well as in prostate tissue that had been subjected to prior combined androgen blockade. We hypothesize that, on appropriate additional mitogenic stimulation, cells in this layer, and other p27(Kip1)-negative basal cells, are competent for rapid entry into the cell cycle. Consistent with the fact that cancer cells are capable of cell division, all cases of high-grade prostatic intraepithelial neoplasia and invasive carcinoma also showed down-regulation of p27(Kip1) as compared with the surrounding normal-appearing secretory cells. In pelvic lymph node metastases, p27(Kip1) expression was also reduced. In summary, our results suggest that lack of nuclear p27(Kip1) protein may delineate a potential transiently proliferating subcompartment within the basal cell compartment of the human prostate. In addition, these studies support the hypothesis that reduced expression of p27(Kip1) removes a block to the cell cycle in human prostate epithelial cells and that dysregulation of p27(Kip1) protein levels may be a critical early event in the development of prostatic neoplasia.